EXTRA NUCLEAR DNA CONTROL REGION AND CYTOCHOME B GENE BASED PHYLOGENY OF KAIL SHEEP BREED OF AZAD JAMMU AND KASHMIR: IMPLICATIONS TOWARDS CONSERVATION - T. Hussain; M. E. Babar; A. Wajid (Journal of Animal and Plant Sciences, 2016)
In the present study, we analyzed two mitochondrial DNA (mtDNA) segments  i.e. partial (564 bp) control region (D-loop) and complete (1140 bp) Cytochrome b (Cyto b) gene in Kail sheep breed raised in Azad Jammu and Kashmir (AJ&K). The phylogenetic analysis of partial mtDNA (564bp) control region revealed two distinct mitochondrial maternal lineages (haplo-groups A and B). However, the haplogroup A was the major lineage found in domestic Kail sheep. The phylogenetic pattern developed from the mtDNA control region was confirmed by the analysis of complete Cyto b. This study confirmed the results of previous reports in the region that the mitochondrial maternal lineages A and B are predominantly found in domestic sheep breeds in Asian countries. Furthermore, this preliminary study provides useful information of phylogenetic analysis and future conservation strategies of Kail sheep in the AJ&K region.
Keywords: Mt DNA control region; Cytochrome b; Haplogroups; Phylogeny; Kail Sheep; Azad Jammu and Kashmir (AJ&K).